PENGAWASAN FASILITAS MEGA WISATA COASTARINA DI KOTA BATAM KEPULAUAN RIAU - Septianingsih, Yola Gress; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
ABSTRACT Supervision is the final function that must be carried out in management. With supervision, it can be seen about the results that have been achieved. The method used in supervision is to compare everything that has been carried out with the standard or plan, as well as making corrections if deviations occur. So with supervision you can measure how far the results that have been achieved are in accordance with what was planned. This research uses a qualitative method that aims to find out more about how the coastarina mega tourism facilities are monitored in Batam City, Riau Islands. This research focuses on the factors that become obstacles in monitoring tourist attraction facilities, starting from how to determine measuring tools, assessment and corrective actions for the tourist attraction. This research uses interviews, observations and documentation to detail the things involved in monitoring mega tourism facilities, with the hope of providing new innovations for tourism development, especially in tourism monitoring. Keywords: Supervision, Facilities, Coastarina Mega Tourism